Dual-resource Constrained Scheduling for Quality Control Laboratories - Cunha, M. (2020)
This work presents a novel formulation for quality control laboratory scheduling considering both equipment and analysts as constraints. The problem is modelled as a dualresource constrained exible job shop problem. The formulation considers analyst's tasks in multiple time points during the processing of samples. The mathematical model is implemented as a mixed integer linear programming model (MILP) aiming to minimize makespan. Two sets of instances for the scheduling problem are developed and solved. The rst instance consists on a small example that illustrates the proposed formulation and is solved to optimality. The second instance mimics the real industrial problem and shows the challenges resulting from growing complexity.